Charging stations‐oriented electric vehicle charging strategy based on battery characteristics. (6th May 2021) - Sun, Lei; Chen, Yanfeng; Li, Wenlong; Deng, Qingxu
Summary: In recent years, electric vehicles (EVs) receive intensive attention due to their environment‐friendly nature and outstanding energy efficiency. However, there are still obstacles in EVs' popularity. Battery related issues are most concerned from users' perspective. While the evolution in battery technology may help to address the aforementioned problems eventually, other solutions are in urgent demand for the time being. In this paper, we propose an innovative charge scheduling method that could significantly improve EV users' charging experience with the nowadays battery technology. Specifically, the proposed method takes into account the characteristics of the batteries to be charged as well as the constraints of the external power grid; thus, a plan can be devised for efficiently allocating the power of the charging station to the EVs through cyber‐physical system. Our method prioritizes jobs based on their marginal utilities to maximize user satisfaction with limited power resource. The power allocation in our method is managed globally and constrained by specific rules to avoid waste or overload in the power grid. Lastly, we simulate several power scheduling methods in charging stations, which validates that the user satisfaction under our method is higher than that of other traditional method.